The Use of Virtual Reality as an Aid Tool in the Implementation of a Radiopharmacy Center in a Nuclear Medicine Service (Brazilian Journal of Radiation Sciences, 2023)
The preparations of radiopharmaceuticals must follow the parameters of quality, efficacy, and safety (pharmaceutical and nuclear), complying with all the requirements established in good manufacturing practices, guaranteed by the physical structure, layout, safety, and radiological protection, which are also fundamental for the correct flow to be followed for excellence in the functioning of the service. One of the main problems is related to the flow of radiopharmaceuticals, which implies exposure to ionizing radiation, which in turn poses serious biological risks to the human body. simple erythema (redness) to the acute radiation syndrome, which can even be lethal. Factors like this corroborate the need for training that simulate real situations, however, situations like this are limited, due to the risk to which a non-specialized professional can be exposed if radioprotection standards are not obeyed. The present work aims to propose and evaluate the use of virtual reality (VR) technology for training and qualification of professionals in a radiopharmacy. The applied methodology was divided into four stages, initially the rules and regulations regarding the Nuclear Medicine Service published by ANVISA, CNEN and international recommendations by the IAEA were analyzed in detail, in the second stage visits were carried out in public and private hospitals in the Rio de Janeiro that present the nuclear medicine service, in the third stage the virtual environment (simulator) was built, and the fourth stage proposed strategies to carry out training, considering a new technique for teaching. The use of virtual reality, through a simulator, allowed the creation of a graphical environment with a realistic appearance, in which the user can navigate in this environment and manipulate the virtual world. Therefore, it is expected that this tool can help in the planning and training of radiopharmacy professionals.
Keywords: Radiopharmacy; Nuclear Medicine; Radiopharmaceuticals; Virtual Reality